Biogas Generation Potential from Swine Manure in the Microregion of Feira de Santana, Brazil - Tiago Silva e Silva; Luiz Henrique Santos Silva; Fillipe Valente Braz; Maylane Neres Costa Santos; Daniel do Carmo Silva Ribeiro; Henrique Nunes Teixeira (JOURNAL OF BIOENGINEERING, TECHNOLOGIES AND HEALTH, 2026)
This study assesses the potential for biogas generation from swine manure in the microregion of Feira de Santana, Bahia, Brazil, an area with significant pig farming activity. The improper disposal of swine manure poses significant environmental risks, including water and soil pollution and the emission of greenhouse gases. This research aims to quantify the energy potential of these residues by applying anaerobic digestion technology. The methodology involved collecting data on the swine population from official sources such as IBGE and ADAB for the year 2018. Theoretical models and stoichiometric equations were used to estimate the daily and annual production of manure, the potential for biogas generation, and its corresponding energy value. The results indicate a significant potential for biogas production, estimated at approximately 16,083 m3/day, with a methane (CH4) content of about 9,650 m3/day. This volume could be converted into approximately 36.67 MWh of electricity daily, assuming a 35% conversion efficiency. The conclusion highlights the technical feasibility and environmental benefits of implementing biodigesters in the region, transforming an environmental liability into a valuable renewable energy asset, contributing to the local energy matrix and promoting sustainable development. The most viable application identified is the use of biogas as a substitute for cooking gas (LPG), offering a rapid financial return for farmers.